2000
DOI: 10.1111/j.1939-165x.2000.tb00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of Estrogen and Progesterone Receptors in Lymphoma of Horses

Abstract: Immunohistochemical techniques were used to examine 29 cases of equine lymphoma for estrogen receptor (ER) and progesterone receptor (PR) expression. The lymphomas examined included T-cell-rich large B-cell lymphomas, B-cell neoplasms, and T-cell lymphomas. The individual cases were also classified according to the anatomic location of the tumors. One normal equine lymph node was also examined for ER and PR expression. All of the cases of equine lymphoma and the normal lymph node were negative for Er. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
10
0
3
Order By: Relevance
“…2000). This study also found that the anatomical location of lymphoma correlated with the percentage of neoplastic cells that had progesterone‐positive receptors (100% of splenic lymphomas, 67% of cutaneous, 60% of thoracic, 40% of multicentric and 25% of alimentary of equine lymphomas had progesterone‐positive receptors) (Henson et al . 2000).…”
Section: Diagnosismentioning
confidence: 65%
See 1 more Smart Citation
“…2000). This study also found that the anatomical location of lymphoma correlated with the percentage of neoplastic cells that had progesterone‐positive receptors (100% of splenic lymphomas, 67% of cutaneous, 60% of thoracic, 40% of multicentric and 25% of alimentary of equine lymphomas had progesterone‐positive receptors) (Henson et al . 2000).…”
Section: Diagnosismentioning
confidence: 65%
“…In mares it has been anecdotally reported that the lesions regress during pregnancy but reappear after foaling (Henson et al . 1998; Henson et al . 2000).…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Previous reports described such receptors on 1 to 10% of tumor cells, but there was no apparent correlation to the hormone produced by an ovarian tumor. 15,16 Thus, the link between hormonal states and neoplastic lymphocyte proliferation or regression remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…12,24,34,40 Subcutaneous forms of lymphoma that regress and recur in response to steroid hormone stimulation have been described. 15,16 In these cases, a small proportion of tumor cells expressed nuclear progesterone receptors, which was implicated to account for cell proliferation in response to hormone binding. 16 Characterization of tissues predominantly from abattoir submissions suggested that most horse lymphomas were of B-cell origin and that presence of 40-80% small T lymphocytes was common.…”
mentioning
confidence: 99%
See 1 more Smart Citation